IMPACT OF THE RISK MANAGMENT AND QUALITY IN TOURISM TRENDS - UKAJ, Fatos (Journal of Environmental Management and Tourism, 2016)
In this paper, the uncertainty and risk are being treated as a result of the unsatisfactory situation in the country's tourist industry and in neighboring countries that affect the level and direction of developments in tourism now and in the future. Not a favorable environment such as: political and security situation, ecological problems, the situation with the epidemic and other health problems, inappropriate economic development and unfavorable situation in all field of traffic, are among the factors of the environment to be analyzed in order to come to conclusions about the current situation and their impact on the development of tourist industry in Kosovo. Now day’s tourism is treated as an economical activity with a constant growth all over the world, this is also expected for Kosovo’s tourism and nearby countries for coming periods of time. In some developed countries tourism is treated as an important exporter and in meantime as an absorber of labor force and this branch is important for softening unemployment. Management with total quality in tourist industry and catering has its own specifics. A big attention should be paid to standards that have to do with quality and insured goods supplied to hotels, and those provided in tourism. Quality care is being placed in the first place, in wholesale of successful touristic enterprises. Here it should be noticed the fact that there is a liaison between the quality, consumers pleasure and consumers loyalty.